1978
DOI: 10.1177/002194367801500202
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Information Flows Within the Superior/Subordinate Relationship

Abstract: This paper examines distortion of information by subordinates and several variables related to distortion. Methodology and results are presented for distortion of upward information leadership roles and accuracy in downward communication. The evidence strongly suggests that certain activities of the superior have an important bearing upon subordinate distortion of information.THE SIGNIFICANCE OF COMMUNICATION to the management of organizations is reflected in both the literature and the common sense of manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Extrapolating on Athanassiades's research, Level and Johnson (1978) have recently found that upward distortion is most likely to be associated with messages in which in-formation about the following personality factors is communicated: ascendency, responsibility, emotional stability, cautiousness, and original thinking. Their data also suggest that in certain areas subordinate tendencies to distort upward communication can be reduced by increasing the superior's "consideration" leadership style, or increasing the accuracy with which the superior transmits downward information.…”
Section: Upward Distortionmentioning
confidence: 91%
“…Extrapolating on Athanassiades's research, Level and Johnson (1978) have recently found that upward distortion is most likely to be associated with messages in which in-formation about the following personality factors is communicated: ascendency, responsibility, emotional stability, cautiousness, and original thinking. Their data also suggest that in certain areas subordinate tendencies to distort upward communication can be reduced by increasing the superior's "consideration" leadership style, or increasing the accuracy with which the superior transmits downward information.…”
Section: Upward Distortionmentioning
confidence: 91%
“…Many studies on information distortion have focused on factors that increase or decrease the level of information distortion within the organizational hierarchy. These factors can be roughly divided into three groups (Dansereau & Markham, 1987): (a) contextual factors, such as organizational climate and structure (Athanassiades, 1973;Bacharach & Aiken, 1977;Curtis, 1989;Jablin, 1982); (b) relationship or social factors, such as trust and interdependence (Larson, 1986;Read, 1962;; and (c) individual difference factors, such as the communicator's upward mobility aspirations (Athanassiades, 1973;Cohen, 1958;Glauser, 1984;Read, 1962;Synder & Zorn, 1986) or the supervisor's leadership and communication style (Level &Johnson, 1978;Luthans & Larsen, 1986). P. Brown and Levinson's (1987) politeness theory also considers how individual, social, and contextual factors affect communication.…”
Section: Contextual Social and Individual Factors Affecting Communimentioning
confidence: 99%